If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(k + -4) = 65 Reorder the terms: -5(-4 + k) = 65 (-4 * -5 + k * -5) = 65 (20 + -5k) = 65 Solving 20 + -5k = 65 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -5k = 65 + -20 Combine like terms: 20 + -20 = 0 0 + -5k = 65 + -20 -5k = 65 + -20 Combine like terms: 65 + -20 = 45 -5k = 45 Divide each side by '-5'. k = -9 Simplifying k = -9
| 6-4r+1=r-5(r-7) | | -3y-2=-5-4t | | 13-2y=7 | | x+0.05x+0.15x=12.5 | | 11x-11/30=10x+23/45 | | s/3-12=15 | | 2a=0.22 | | 3+8x=3x(2x-1) | | Y=0.04(3) | | 7^2-24/3 | | (x+h)k=z | | Y=0.04(2) | | y=3.08sqrt(5)+20.08 | | 9z-z=-1+5z-3-5 | | -3v=9/7 | | Y=0.04(1) | | 60+5x=135-10+x | | 3(1+2x)=69 | | -6/5y=12 | | y=1/2(2)-6 | | 2w+2(w+19)=1291/2 | | y=10x^2-20x+11000 | | y=1/2(3)-6 | | -4/7v=16 | | y=1/2(1)-6 | | 4(r+2)=-5r+26 | | 0.5n+6=0.33333n | | 5x+40x-5=9(5x+9) | | 8t-16-t=5+7t | | 6=.083v | | c=2*3.15*r | | -2x+5+6x=33 |